Three-dimensional ultrastructure of the brain pericyte-endothelial interface. Issue 9 (September 2021) - Ornelas, Sharon; Berthiaume, Andrée-Anne; Bonney, Stephanie K; Coelho-Santos, Vanessa; Underly, Robert G; Kremer, Anna; Guérin, Christopher J; Lippens, Saskia; Shih, Andy Y
Pericytes and endothelial cells share membranous interdigitations called "peg-and-socket" interactions that facilitate their adhesion and biochemical crosstalk during vascular homeostasis. However, the morphology and distribution of these ultrastructures have remained elusive. Using a combination of 3D electron microscopy techniques, we examined peg-and-socket interactions in mouse brain capillaries. We found that pegs extending from pericytes to endothelial cells were morphologically diverse, exhibiting claw-like morphologies at the edge of the cell and bouton-shaped swellings away from the edge. Reciprocal endothelial pegs projecting into pericytes were less abundant and appeared as larger columnar protuberances. A large-scale 3D EM data set revealed enrichment of both pericyte and endothelial pegs around pericyte somata. The ratio of pericyte versus endothelial pegs was conserved among the pericytes examined, but total peg abundance was heterogeneous across cells. These data show considerable investment between pericytes and endothelial cells, and provide morphological evidence for pericyte somata as sites of enriched physical and biochemical interaction.